Building collaboration in humanitarian operations: the role of institutional work - Silva, Renata de Oliveira (2016)
This study aims to show the value of adopting institutional work as a theoretical lens to better understand the process of collaboration building in humanitarian operations. Studying the institutional work engaged by humanitarian operations and oriented toward collaboration between International Humanitarian Non-Government Organization and local organizations can shed light on the strategies and practices that have a potential to improve collaborations in complex and risky contexts. In this sense, the objective of this research is to answer the following question: How institutional work might contribute to improve our understanding about collaboration between IHNGOs and local organizations in humanitarian operations? To explore this issue, I invited a number of participants to share their experience, difficulties and ideas on how collaboration emerges between IHNGO and local organizations. I conducted 30 in-depth interviews with humanitarian workers from the biggest and most influence international humanitarian organizations, people with great experience that participated in the most challenging humanitarian operations in the last 10 years. The main contributions of this work is to provide a repertory of humanitarian institutional works and to highlight the ways in which power and trust – two conceptual elements suggested by the literature review – are mobilized by social actors to engage in collaboration in humanitarian operations.